Prunus americana American Plum: FPS492/FP492, 6/2007 - Gilman, Edward (EDIS, 2007)
This document provides a detailed overview of the American plum (Prunus americana), a native North American tree. It describes the tree’s physical characteristics, including its height, spread, and seasonal changes, such as its white spring flowers and yellow fall foliage. The document also covers the tree’s growth habits, soil and light requirements, and its uses in landscaping. Additionally, it highlights the tree’s resilience to drought and various soil types, while noting its tendency to form multi-stemmed thickets. The document concludes with information on propagation methods and potential pest issues.